ANALYSIS OF BIODIVERSITY AND QUALITY OF METRO RIVER IN MALANG CITY (PLANKTON AND BENTOS BIOINDICATOR STUDY) - Hery Setyobudiarso; Endro yuwono (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2018)
Metro River is a river that passes through Malang City and empties into Karangkates Dam. The increasing number of residents of Malang City resulted in more volume of waste water produced, and one of them is dumped on the Metro River. This affects the increasing pollution load received by the river so that it affects the decreasing of tamping capacity of river pollution load. Changes in water quality in rivers lead to changes in macrozoobenthic community composition. Therefore, it is necessary to monitor the quality status of Metro River by using macrozoobentos animals. The purpose of this research is to make the classification of Metro River based on macrozoobentos animal community in determining the water quality status of Metro River based on macrozoobentos and the classification of pollution level that happened. The research method is field observation, water quality measurement of Metro river and macrozoobentos sampling. The results showed that the distribution of macroinvetebrata in the Site of group of Banana Temple was from Gastropoda family, Leptophlebiidae, Chloroperliidae, and Baetidae on rocks with fast current velocity (1.02 m3 / s), 17-27 ° C, BOD level 3.7 mg / l, and COD content of 20.8 mg / l. While on the Site of group Merjosari, Karang Besuki, Bandulan and Sitirejo were found macrozoobentos from Chironomidae, Hydrop sychidae and Lumbri cullidae families, on the substrate of mud and sand, with slow flow rate (0.0052 - 0.0675 m3 / s), BOD 21, 8 - 45.7 mg / l, and COD content 107.8 -267.2 mg / l. The status of upper Brantas river waters determined by using the BMWP Index of the Pisang Candi, Merjosari, Karang Besuki, Bandulan and Sitirejo groups has medium gray water status with ASPT values ranging from 4 to 6.2.  Keywords: macrozoobentos, Water Quality Status of River, BOD, COD